Pelatihan Life Skill Pembuatan Abon Ikan Nila sebagai Produk Unggulan Desa Peresak Kabupaten Lombok Barat - Swandayani, Rosalina Edy; Sulastri, Meilinda Pahriana; Cahayani, Mimi (LPPM Universitas Pendidikan Mandalika (UNDIKMA), 2024)
This activity aims to improve the community skills in processed the Nila fish to be superior village products. The method for implementing this service was socialization and training with partners, namely the Mina Jaya Abadi Fish Cultivator Group in Peresak Village, West Lombok Regency. Evaluation of activities was carried out by giving pre-tests and post-tests to participants to measure the activities is success. The result of the activity was the community could make the Fish Floss from Nila fish. The results of this service showed that members of the Mina Jaya fish cultivator group had the knowledge and skills to processed Nila Fish into Fish Floss with economic value. Also, partners were able to operate the Spinner and Freezer equipment provided by the PKM team so that the fish floss produced is more hygienic and healthier.